DEVELOPMENT OF DISASTER PREPARED SCHOOL CULTURE THROUGH IMPLEMENTATION OF DISASTER MITIGATION - Safrida Safrida; Niswanto Niswanto; Khairuddin Khairuddin (Universitas Nurul Jadid, 2025)
This study examines the concept of educating with the heart from the perspective of Ibn Qayyim al-Jawziyyah and its implications for modern education. The research is grounded in the concern that contemporary education often emphasizes cognitive achievement while neglecting moral, emotional, and spiritual dimensions. Therefore, this study aims to explore how heart-based education can provide a more holistic educational framework. This research employs a qualitative library research approach using philosophical and conceptual analysis. Primary sources include major works of Ibn Qayyim, while secondary sources support the interpretation and contextualization of his educational thought within modern educational discourse. Data were analyzed through content analysis to identify key themes related to heart-based education and its practical implications. The findings reveal that educating with the heart emphasizes compassion, sincerity, empathy, understanding of human nature (fitrah), gradual discipline, and reliance on prayer. These principles contribute to the development of balanced individuals by integrating cognitive, affective, and spiritual aspects. In modern education, this concept implies the need for student-centered learning enriched with moral and spiritual values, reflective practices, and character-based evaluation systems. It also redefines the role of teachers as moral guides, not merely knowledge transmitters. The concept of educating with the heart is highly relevant to modern education as it addresses moral and spiritual gaps while supporting holistic human development. However, this study is limited to a conceptual framework and lacks empirical validation. Future research is recommended to apply this concept in educational settings and to conduct comparative and empirical studies for broader applicability.